Factors That Affecting The Accounting Fraud In Kediri Cooperatives, Tabanan - Susandya, Anak Agung Putu Gede Bagus Arie; Suwandewi, Putu Ayu Meidha (Cattleya Darmaya Fortuna, 2024)
The study aims to empirically investigate the influence of pressure, the effectiveness of internal controls, compensation adequacy, management ethics, also adherence to accounting regulations on the inclination towards accounting fraud within cooperatives in Kediri District, Tabanan Regency. It involves employees from cooperatives operational for over a decade, with a sample size of 82 selected through purposive sampling. Multiple linear regression analysis is employed to test the hypotheses. Results reveal a positive impact of pressure on accounting fraud inclination, while the effectiveness of internal controls, compensation adequacy, management ethics, also compliance with accounting regulations negatively affect fraud propensity. Future research could expand the study's scope by considering additional variables, such as management's ethical culture, may influence accounting fraud tendencies.